(untitled) (Journal of University of Babylon for Engineering Sciences, 2025)
Moving bed bioreactor technology is one of the innovative solutions in wastewater treatment, which merges efficiency in biological treatment with design flexibility. This technique is based on the use of tiny plastic carriers (media) that freely move inside the reactor, providing a large surface area for the creation of biofilms containing microorganisms responsible for the breakdown of organic wastes and nutrients like phosphorus and nitrogen. Salient benefits from MBBR technology include handling variable organic loads, less land area compared to conventional systems like activated sludge, and a reduction in energy consumption. It also finds its application in various fields that include domestic and industrial wastewater treatment-related segments, such as food and pharmaceutical industries, and even the reuse of treated water for irrigation or any other industrial purpose. For these objectives to be reached, several technological challenges still have to be addressed, such as the improvement of carriers’ distribution inside the reactor, the avoidance of clogging of biofilms, and pollutant removal efficiently under extreme conditions. Recent developments in carrier design, including hybrid or nanomaterials, along with the possible combination of MBBR technology with other advanced technologies, like as UV sterilization or reverse osmosis, have improved performance. The current research tries to give a general review of the MBBR technology and its role in wastewater treatment. Further, it analyzes the scientific research published about MBBR technology by using VOSviewer to: Explore the research trends within the sphere, analyze the scientific citations to identify the most important research sources. Investigate research cooperation at the country and institutional levels and identify the main researchers and influential scientific journals in this specialty. In such a way, the current study is supposed to present the development of scientific research about MBBR technology and may contribute to orienting future studies toward the most important aspects to be improved.